Impact of Different Dental Implant Alloys and Coating Materials on the Health of Tissues Surrounding Implants: a Systematic Literature Review - Ksenija Matvijenko; Alma Pranckeviciene; Rokas Borusevicius (eJournal of Oral Maxillofacial Research, 2024)
Objectives: Recently surface modification techniques have been introduced to dental implants to improve osseointegration, bone formation at the implant surface, and to reduce the occurrence of mucositis and peri-implantitis. The aim of this systematic literature review was to investigate the dependence of the risk of inflammation of the tissues surrounding the implant on different implant alloys and surface coating materials.